IMPLEMENTASI MOTIVASI 3.0 DALAM SISTEM PENGENDALIAN MANAJEMEN UNTUK MENGATASI MOTIVATIONAL PROBLEMDI RUMAH MAKAN PANGSIT MIE UP 90 - Arief Kalisda; Wiyono Pontjoharyo (CALYPTRA, 2018)
Abstract - The management controlling system helps business entity to handle the control problem that happen in the business entity. In solving the control problem, where the control problem itself is the problem of intrinsic motivation of their employee. Hence, the business entity need to implement motivation 3.0 through management control system of business entity. Motivation 3.0 focus on learning about intrinsic motivation that solve the intrinsic motivation problem, which can lowered the performance of business entity. Therefore, this research want to focus on how to implement motivation 3.0 into management control system in order to solve the control system that occur in business entity. The approach that use in this research is qualitative approach with the purpose of research is explanatory research. The benefit of this research is applied research. In order to get the accurate data, we need to do interview, observation, and document analysis. The outcome of this research is the implementation of motivation 3.0 management control system to handle motivational problem, so that the result of this research can improve the performance of the employee because of the effective management control system in solving the motivation problem.